Amplifying the Religious Moderation from Pesantren: A Sketch of Pesantren’s Experience in Kediri, East Java - Titis Thoriquttyas; Farida Hanun (Analisa: Journal of Social Science and Religion, 2020)
One of the issues which has been attracted by Muslim scholars is the religious moderation mainstreaming. Pesantren, as the oldest and indigenous educational institution in Indonesia, is inseparable from such issue. This study examines the development of moderation a basic idea of pesantren. This paper is divided into three parts. First is introducing the articulation of moderation in pesantren from various perspectives. Second is discussing the idea of Arkoun and al Jabiri’s ideas and its relation on moderation and pesantren. Third is elaborating the moderation of pesantren from its curriculum’s and extracurricular activities. This paper concerned on how Islamic moderation has shaped and disseminated through the learning process in pesantren?. Furthermore, this research was conducted at ﬁve pesantren in Kediri, East Java by considering their typologies and management. By using the interview method, literature study and in-depth observation, this research has produced data related to the research theme. Then, the results of research are to explore the complexity and continuity of Islamic moderation in pesantren and to prove that moderation mainstreaming in the grassroot is not static but ﬂexible and dynamic as well as being ﬂuid and multi-dimensional through the learning process and the extracurricular activities.